Thyroid Hormone Status Regulates Skeletal Muscle Response to Chronic Motor Nerve Stimulation - Zhou, Jin; Parker, Daniel C.; White, James P.; Lim, Andrea; Huffman, Kim M.; Ho, Jia Pei; Yen, Paul M.; Kraus, William E. (Frontiers in Physiology, 2019)
ABSTRACT Although both exercise and thyroid hormone (TH) status can cause cellular and metabolic changes in skeletal muscle, the impact of TH status on exercise-associated changes is not well understood. Here, we examined the effects of TH status on muscle fiber type, cell signaling, and metabolism in a rabbit model of exercise training — chronic motor nerve stimulation (CMNS). Five rabbits were rendered hypothyroid for seven to eight weeks and three rabbits were made hyperthyroid for two weeks prior to CMNS of the left peroneal nerve for ten days. We then measured protein markers of muscle fiber type, autophagy, and nutrient- or energy-sensing, including metabolic intermediates. CMNS increased MHC-I expression in hypothyroid rabbits, whereas it was unchanged in hyperthyroid rabbits. CMNS also increased p-AMPK, p-ATGL, CPT-1α, p-Akt, GLUT4, and p-70S6K in hypothyroid rabbits. In contrast, p-AMPK and p-ATGL were increased at baseline in hyperthyroid rabbits, but CMNS did not further increase them or any of the other markers. CMNS also increased TCA cycle and acylcarnitine metabolites in hypothyroid rabbits; whereas, acylcarnitines already were elevated in hyperthyroid rabbits, and were only slightly increased further by CMNS. In summary, CMNS effects on cell signaling and metabolism of skeletal muscle were more pronounced in the hypothyroid than the hyperthyroid state. Interestingly, in the hypothyroid state, CMNS caused concomitant activation of two signaling pathways that are usually reciprocally regulated — AMPK and mTOR signaling — manifest as increased -oxidation, MHC-I expression, and protein synthesis. Thus, our findings provide insight into the role of TH status on exercise response in muscle. Our observations suggest that TH status of patients may be an important determinant and predictor of their response to exercise training responses in skeletal muscle.